Emerging Roles of Periodontal Pathogen–Derived Outer Membrane Vesicles in NAFLD - Congcong Lv; Kaikai Shi; Yadong Guo; Zixin Guo; Pingchan Luo; Lijing Wang; Zhe Wu; Pei Yu (International Dental Journal)
The rising incidence of nonalcoholic fatty liver disease (NAFLD) poses a great socioeconomic burden worldwide. Also, periodontitis is the most common chronic inflammatory disease caused by a group of oral pathogens, affecting both oral health and systemic conditions, especially liver disease. Although accumulating evidence has elucidated an association between periodontal pathogens and NAFLD, the role of periodontal pathogen–derived outer membrane vesicles (OMVs) has not yet been clarified. In this comprehensive review, we aim to address this gap by summarising the progression and pathogenesis of NAFLD and revealing the relationship between periodontal disease and NAFLD multidimensionally. Additionally, this review sheds light on the multifunctional roles of periodontal pathogens OMVs and emphasises that periodontal pathogen–derived OMVs promote the development of NAFLD by stimulating Kupffer cells to produce inflammatory factors and inducing the activation of Hepatic stellate cells. However, it is still controversial whether periodontal pathogen–derived OMVs can be transferred to the liver through the bloodstream route or the oral-gut-liver axis. This highlights the pressing need for continued research efforts to develop new and optimised research schemes to observe the formation of the systemic distribution pathway of periodontal pathogen–derived OMVs. Finally, it is notable that there are currently no relevant clinical treatment guidelines to make specific provisions on controlling the level of periodontal pathogen–derived OMVs in patients with NAFLD. Guidelines developed based on our findings may contribute to the standardisation of practices. It can also provide effective strategies and potential therapeutic targets for NAFLD patients with periodontitis to alleviate the development of NAFLD diseases by inhibiting periodontal pathogens OMVs.